2004
DOI: 10.1111/j.1440-1681.2004.04088.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Bioremediation: From Enzyme Discovery to Applications

Abstract: 1. Enzymatic bioremediation is potentially a rapid method of removing environmental pesticide residues. Applications include the treatment of residues resulting from agricultural production and processing industries, such as the treatment of irrigation waters, surface-contaminated fruit and vegetables and spent dip liquors. 2. A specific application for some organophosphate-degrading enzymes involves detoxification of nerve agent stockpiles. Effective and affordable remediation requires highly specialized enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 31 publications
1
86
0
1
Order By: Relevance
“…Nonetheless, microbial degradation is considered the major determining factor of the organophosphrus fate in the environment and is often the main process of pesticide degradation in soils, representing the safest, least disruptive and most cost-effective treatment method [30,31]. The results of the present study revealed that fungal degradion of profenofos, diazinon and malathion increased with increasing incubation peroid but at the same time decreased with increasing initial concentrations of insecticides (Tables 5 and 6).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, microbial degradation is considered the major determining factor of the organophosphrus fate in the environment and is often the main process of pesticide degradation in soils, representing the safest, least disruptive and most cost-effective treatment method [30,31]. The results of the present study revealed that fungal degradion of profenofos, diazinon and malathion increased with increasing incubation peroid but at the same time decreased with increasing initial concentrations of insecticides (Tables 5 and 6).…”
Section: Resultssupporting
confidence: 53%
“…The effects of different temperatures (20,25,30,35 and 40°C) on diazinon, profenofos and malathion biodegradation in the mineral salts medium are presented in Tables 7 and 8 Means followed by the same letters are not significantly different in each insecticide; -ve, growth not detected 18.01 ± 0.65a 0.0 ± 0.0c 0.00 ± 0.0b 0.00 ± 0.0b Means followed by the same letters are not significantly different in each insecticide The results showed that the increase in temperature enhances the degradation rate of diazinon, profenofos and malathion up to 30°C and 35°C with using M. anisopliae and trichoderma respectively. Recently, it has been reported by many researchers that optimization of different environmental factors can play a vital role in accelerating the process of insecticides biodegradation [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Bioremediation technologies potentially have four types of applications involving the cleanup of contaminated soils, liquid wastes, stockpiles, and commodities (149,171). All four are relevant to HCH, even though it is no longer in widespread use as an insecticide.…”
Section: Hch Bioremediationmentioning
confidence: 99%
“…Two closely related (~90 % sequence identity) bacterial phosphotriesterases have been extensively characterised: OpdA from Agrobacterium radiobacter [56], and OPH from Pseudomonas diminuta [57] and Flavobacterium [58]. Field trials of OpdA as a bioremediation agent have been conducted [4], and it is already in use as a commercial product to detoxify OP residues in various contaminated wastes, sold under the brand name LandGuard TM from Orica Watercare (Australia) at a cost to user considerably lower than the pesticides themselves.…”
Section: Phosphotriesterases: Oph Opda (Ec 318)mentioning
confidence: 99%
“…The subject of pesticide bioremediation has been considered in several excellent recent reviews covering bioaugmentation, biostimulation [2,3] and enzymatic bioremediation [3,4].…”
Section: Introductionmentioning
confidence: 99%